Physiology of wrestlers` dehydration - Asim Cengız; Bilal Demirhan (Türk Spor ve Egzersiz Dergisi)
Rapid weight loss via dehydration has profound adverse effects on the wrestler's physiology and muscularendurance even with %1 of body weight loss. Additionally, there is a decline after 4% of weight loss in strengthor anaerobic power performance. However, these adverse effects do not seem to impair muscle strengthduring high-power exertions lasting less than 30 seconds. In fact, for athletes participating in brief-duration,high- power sports, rapid weight loss may give them an advantage by increasing power on a pound for poundbasis. But, as strenuous exercise is extended, environmental temperatures rise, and degree of dehydrationincreases performance will ultimately suffer. The negative effects of dehydration on cardiovascular fitnessparameters seem to repair faster compared to strength and power values. Several studies indicated whileweight cycling has acute effects on performance, augmentation in body weight and muscular performance ofthe wrestlers occurs subsequent to the wrestling season. Several studies also indicated some negativepsychological effects of dehydration on wrestlers' performance: increased fatigue, anger, and anxiety,decrements in mood and motivation, and increased confusion. Still, more studies are needed in these areas.Weight loss due to the dehydration can potentially affect wrestlers' health negatively. However, it was foundthat there are no considerable health effects of dehydration on wrestling. However, more studies are needed tostrengthen these results since there are not many studies about the long-term effects of dehydration onhormonal, psychological and health status of wrestlers.